A novel approach to determining pulmonary valve replacement timing in repaired tetralogy of Fallot patients - Delaney, Laura; Browne, Andrew; Veldtman, Gruschen R.; Huang, Sihong (International journal of cardiology congenital heart disease, 2025)
Here we propose a novel approach to determine a patient-specific optimal time for pulmonary valve replacement (PVR) in patients with repaired tetralogy of Fallot (rTOF) based on a mathematical technique known as optimal stopping theory. We outline, in a theoretical framework, how we would apply the proposed timing rule for PVR in patients with rTOF. We define each of the model input variables specific to PVR, and we describe how the model can be assessed for its suitability for use in clinical practice to guide timing of PVR in patients with rTOF. In this manuscript we demonstrate, for the first time, an application of a timing rule derived from a mathematical technique known as optimal stopping theory to determine the optimal time to perform PVR in patients with rTOF. Using the technique, we derive two patient-specific-thresholds on clinical status based on patient specific risk factors. PVR is recommended if at the time of assessment, a patient's clinical status lies between the thresholds. Otherwise, they are either too well or too unwell to undergo PVR. Current clinical practice guidelines for timing of PVR in patients with rTOF remains flawed and has since been challenged. We believe the timing rule is a suitable approach to complement current medical guidelines on when to perform PVR in patients with rTOF on a patient-specific level. To determine its suitability for generalized application in clinical practice, we intent to validate it retrospectively using large clinical cohort(s) who have undergone PVR for rTOF.